Crab and shellfish occurrences in the newly-grown mangrove habitats in southern Thailand. (April 2018) - Yeesin, P; Bautip, S; Chesoh, S
Abstract: Mangrove crabs and shellfish populating in Prince of Songkla University's new grown mangrove forest were investigated from January 2011 to December 2011 and then repeated annually. A total of 12 species under 6 families of crab and 11 species under 5 families of shellfish were recorded. The most abundant family of crab was Sesarmidae (64.18 %), followed by Ocypodidae, Varunidae, Macrophthalmidae, Portunidae and Dotillidae. Episesarma mederi ( H. Milne Edwards, 1853) showed highest dominant species. In addition, the most dominant family of shellfish was Potamididae (13.79 %), followed by Melampidae, Assimineidae, Onchidiidae and Littorinidae. Sea snail ( Cerithidae quadrata ; Sowerby, 1866) presented the most dominant coastal mollusc species. Abundance and diversification crabs and mollusks show important component of food web of this type ecosystem. However, only trapped hold samples during low tide were collected but this preliminary finding enables reasonable specified regulation measures.